Water quality for irrigation in the Huallaga basin, Peru - Cerna-Cueva, Alberto Franco (2022)
The objective of this study was to evaluate the quality of surface water used for irrigation in the Huallaga basin. We worked with water quality monitoring data in the basin conducted by the National Water Authority (ANA) counting 139 monitoring points, evaluating 41 parameters for the period 2014 - 2019, the Peruvian Water Quality Index (ICA - PE) intended for irrigation was calculated, using as reference values the Environmental Quality Standard (ECA) for surface water in category 3 D1 (irrigation water). Of the 139 monitoring points, 26 (18.71%) were of excellent quality, 62 (44.60%) of good quality, 35 (25.18%) of fair quality, 13 (9.35%) of poor quality and 3 (2.16%) of very poor quality. The main contaminants found were thermotolerant coliforms, Escherichia coli, which on average exceeded the ECA by 606 and 288 times and by 53.4% (1029/1927) and 38.9% (701/1803) respectively. Contamination by organochlorine pesticides, in 100% (10/10) of the chlordane measurements the RCT was exceeded and with respect to Endrin, Aldrin and DDT the RCT was exceeded in 40% (10/25). The pH, in 25.6% of the measurements the water was outside the ranges tending to alkalinity and for manganese, iron and aluminum, exceeded the ECAs in 17.7%, 13.3% and 11.2% respectively. The main contaminant sources are agricultural and municipal wastewater and the presence of critical points of solid waste.